Prevalence of Oral Squamous Cell Carcinoma, Class 3 Malocclusion and Various Cystic Lesions of Jaw in a Known Population - Chakraborty, Bidyut; .P.U, Bejoy; Bajpai, Ranjan; Bajpai, Chandni; Nair, Divya; Keshav, Handge (Journal of Neonatal Surgery, 2025)
Background: This study was conducted to assess the Prevalence of Oral Squamous Cell Carcinoma, Class 3 Malocclusion and Various Cystic Lesions of Jaw in a Known Population. Material and methods: This study comprised of 100 subjects. The study procedure was explained to all the participants and informed consent was taken from all subjects. All the participants underwent oral clinical examination. The prevalence of oral squamous cell carcinoma, class 3 malocclusion and cystic lesions of jaw was assessed. The findings were tabulated and compared. Statistical analysis was conducted using SPSS software. Results: In this study, oral squamous cell carcinoma was seen in 33 subjects, class 3 malocclusion was seen in 42 subjects and cysts were evident in 25 subjects. Out of 25 subjects having cysts, 12 subjects presented with odontogenic keratocyst, 8 patients presented with dentigerous cyst and 5 subjects had radicular cyst. In group 1, 33 patients with oral squamous cell carcinoma were present. 42 subjects with class 3 malocclusion were present in group 2 and 25 subjects with cysts were present in group 3. In this study, there were total 55 males and 45 females. There were 21 males and 12 females in group1, 23 males and 19 females in group 2 and 11 males and 14 females in group 2. Conclusion:The results of the study conclude that the prevalence of oral squamous cell carcinoma, class 3 malocclusion and cysts was 33%,42% and 25%, respectively. The most common type of cyst was odontogenic keratocyst. The conditions were more common in males as compared to females.